Espetáculos e espontaneidade: um estudo sobre experiências de consumo no turismo - Zuanazzi, Laura Tonon (Universidade do Vale do Rio dos Sinos, 2017)
The consumption experience studies lie on two different streams. The first one, supported by the experiential marketing, states that the interaction with consumers must be filled with constant stimulations that generates surprise and enchantment. The second one criticizes this idea suggesting that this process infantilizes the consumer; rather, it assumes that customers look for freedom to cocreate their own experiences. Regarding the tourism context, the construction of the experience by the companies can be drew in one or other scenario, leading to the question about which one have the best acceptance by consumers. The main objective of this dissertation is to comparatively analyze spectacular experiences versus spontaneous experiences in tourism and try to comprehend what are the points that put them together or that drive them away from each other. For this purpose, a qualitative research was conducted, inspired by the action-research methodology. The goal was to analyze, during the consuming process, the customers reactions and perceptions in both types of experience. The results were divided into macro categories – positive and negative – and specific subcategories in each scenario. Lastly, a comparative analysis between the categories showed the existence of a thin line that separates the perception of positive and negative in the two different approaches. This study instigates theoretical contributions that criticize the existence of a dichotomy between both lines and argues that both paths should complement each other and coexist. Under the companies’ perspective, the results exhibited a set of practical suggestions that support the construction of positive consuming experiences in tourism.
Keywords: Experiência de consumo; Marketing experiencial; Turismo de experiência; Consuming experience; Experiential marketing; Experiential tourism; ACCNPQ::Ciências Sociais Aplicadas::Administração